Risk of extrahepatic cancer in a nationwide cohort of hepatitis C virus infected persons treated with direct‐acting antivirals. Issue 3 (11th May 2021) - Lybeck, Charlotte; Bruce, Daniel; Montgomery, Scott M.; Aleman, Soo; Duberg, Ann‐Sofi
Summary: Background and aims: Direct‐acting antivirals (DAAs) against HCV have an immune modulatory effect, this could possibly lead to a decreased tumour control. We, therefore, aimed to assess the risk of extrahepatic cancer (EHC) during and the first years after DAA treatment. Methods and Results: This is a nationwide cohort study with prospectively collected data for 19 685 persons with HCV, 4013 DAA treated, 3071 interferon (IFN) treated and 12 601 untreated, from 2008 to 2016. Follow‐up time was maximum 3 years. The risk for EHC was compared between the groups using Cox regression analyses, with adjustment for age and Charlson Comorbidity Index (CCI). The HCV‐infected groups were also compared with matched cohorts without HCV from the general population. In total 341 EHCs were identified, 84, 43 and 214 EHC in the DAA, IFN and untreated group respectively. The EHC risk in DAA treated compared with IFN treated was doubled, but when adjusted for age and CCI the HR was 1.07 (95% CI 0.74‐1.56). Compared with the general population, the HR of EHC for the DAA group was 1.45 (CI 1.13‐1.86), with the difference remaining statistically significant after adjusting for CCI. Conclusion: We found no increased risk for EHC associated with DAA therapy after adjustment for age and CCI. An increased risk of EHC in DAA treated compared with the general population was though seen, and attention should be paid to this association in the ageing population with a history of HCV infection.